2022
DOI: 10.3390/polym14020266
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanoparticles from Coir Pith Synthesized by Acidic Sol-Gel Method Improve Germination Economics

Abstract: Lignin is a natural biopolymer. A vibrant and rapid process in the synthesis of silica nanoparticles by consuming the lignin as a soft template was carefully studied. The extracted biopolymer from coir pith was employed as capping and stabilizing agents to fabricate the silica nanoparticles (nSi). The synthesized silica nanoparticles (nSi) were characterized by ultraviolet–visible (UV–Vis) spectrophotometry, X-ray diffraction analysis (XRD), Scanning Electron Microscope (SEM), Energy-Dispersive X-ray Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…The mass reduction of bio-synthesized silica nanomaterials was assessed by the exothermic peak in the DTA curve. The similar results were reported by Maroušek et al, (2022) and Sankareswaran et al, (2022).…”
Section: Characterization Of Sinpssupporting
confidence: 91%
“…The mass reduction of bio-synthesized silica nanomaterials was assessed by the exothermic peak in the DTA curve. The similar results were reported by Maroušek et al, (2022) and Sankareswaran et al, (2022).…”
Section: Characterization Of Sinpssupporting
confidence: 91%
“…The silica nanoparticles are found as aggregates with spherical morphology. Similarly, Maroušek et al, (2022) reported that spherical shape of silica nanoparticles and con rmed by scanning electron microscopy.…”
Section: Sem Analysismentioning
confidence: 81%
“…Among the physicochemical characteristics, nanoparticle sizes primarily influence biodistribution. Typically, nanoparticles with diameter greater than 200 ​nm activate the complement system and are quickly removed from the bloodstream, accumulating in the liver and spleen, while particles with diameter smaller than 10 ​nm are rapidly removed by kidneys [ 49 ]. Consequently, tailoring MSN size allows to achieve the required accumulation in the target tissue and to avoid the rapid clearance from the bloodstream by the mononuclear phagocyte and the reticuloendothelial system.…”
Section: The Multifunctional Project Using Msnsmentioning
confidence: 99%